2013
DOI: 10.3109/10428194.2013.813503
|View full text |Cite
|
Sign up to set email alerts
|

Venous access catheter-related thrombosis in patients with cancer

Abstract: Patients with cancer are at high risk for developing venous thromboembolism (VTE), and the presence of a central venous catheter (CVC) further increases this risk. CVC-related VTE has serious implications related to the loss of vascular access, development of pulmonary embolism, recurrent VTE, infections and post-thrombotic syndrome. The pathogenesis of CVC-related VTE is complex and multifactorial, with risk factors associated with the catheter, the vessel selected for insertion and the underlying cancer as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 94 publications
0
12
0
3
Order By: Relevance
“…Although CVC has the advantages of safety and convenience, the complications of CVC represented by CVC-related thrombosis have also been reported ( 32 ). The incidence of PICC-related thrombosis is closely related to the type of central venous catheter ( 33 ). In addition, the incidence of TE is related to the thickness of the catheter; the thicker the central venous catheter, the higher the incidence of VTE, and the more serious the damage to the vascular epidermis ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although CVC has the advantages of safety and convenience, the complications of CVC represented by CVC-related thrombosis have also been reported ( 32 ). The incidence of PICC-related thrombosis is closely related to the type of central venous catheter ( 33 ). In addition, the incidence of TE is related to the thickness of the catheter; the thicker the central venous catheter, the higher the incidence of VTE, and the more serious the damage to the vascular epidermis ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for VTE include the need of a central venous catheter and use of G-CSF in up to half of the patients 53 , 57 , 58 . Studies have shown that there is a 0.3% to 28% incidence of catheter related VTE in patients with cancer 57 . In addition, the use of G-CSF increases the risk of VTE by 1.69 (range: 1.09-2.64) 54 .…”
Section: Tolerabilitymentioning
confidence: 99%
“…Kateterle ilişkili tromboz sıklığı uygulanan kateterin türüne, kateterin yerleştirildiği damara, kanser türüne ve uygulanan kanser tedavisine göre değişkenlik gösterir (43). Rehberler kateter seçiminde hasta özelliklerinin, uygulanacak kemoterapi türünün ve süresinin öncelikle göz önünde bulundurulmasını önermektedir.…”
Section: Kateterizasyonunclassified